Speak easily - Sedgwick, Edward, 1892-1953; Keaton, Buster, 1895-1966; Durante, Jimmy, 1893-1980; Spence, Ralph, 1889-1949.; Kelland, Clarence Budington, 1881-1964.; Metro-Goldwyn-Mayer; Buster Keaton Productions; Cinetel Films ([Beverly Hills, CA] : Metro Goldwyn Mayer, 1932)
A serious-minded professor inherits $750,000 and decides to cut loose and see the world. He falls in love with an actress and finances the show she is to star in. Life is wonderful until he discovers that the letter announcing his inheritance was a fake. This is Buster's best sound film, but a far cry from his silent work.
Originally released as a motion picture in 1932.
Buster Keaton, Jimmy Durante, Ruth Selwyn, Thelma Todd, Hedda Hopper.
Director of photography, Harold Wenstrom ; editor, William LeVanway.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 20, 2015).
Keywords: Men -- Conduct of life -- Drama; Inheritance and succession -- Drama; Rich people -- Drama; Entertainers -- Drama; Comedians -- Drama; Man-woman relationships -- Drama; College teachers -- Drama; Vaudeville -- Drama; Fortune hunters -- Drama; Slapstick comedy films; Comedy films; Fiction films; Feature films; Internet videos; Streaming video